Activated Carbon Aided Alum Coagulation For Removal Of Textile Dye From Dye Water - Er, Eng Kien (Universiti Sains Malaysia, 2006)
The processes of adsorption followed by coagulation was evaluated for the removal of three textile dyes (CIBACRON Yellow C5G, Remazol Blue RGB and Remazol Red RGB) from water in a laboratory-scale experiment. The adsorption efficiency of manufactured powdered activated carbon (Malbon R4) for three dye solutions was also investigated. Batch experiments showed that the adsorption of dyes increased with an increase in dye concentration and carbon dose. The right sequence of operation was identified for the combined treatment system. The results indicated that maximum percentage of dye removal by adsorption on Malbon R4 for the dyes achieved was 52.15- 83.53 %. The maximum dye removal efficiencies for 20 mg/l and 50 mg/l of dye concentration (for three dyes) with adsorption followed by coagulation were 96.16-99.78% and 96.71-99.60 %, respectively. The combined adsorption-coagulation process has the capability of near complete dye removal. More research should be done with different types of activated carbons and coagulants for removal of dye from dye wastewater.